PERGESERAN CITRA PADA IKLAN SABUN KECANTIKAN - Puji Muryati; Yunizir Djakfar; Darwadi MS (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2021)
The Lux Botanicals 2020 ad, starring MaudyAyunda as the brand ambassador. Previously, Lux exposed her model body more as an attraction that convinced consumers that Lux is a beauty soap product that can support women's beauty. In the advertisement for Lux Botanicals 99% Kill bacteria, MaudyAyunda's version presents a narrative that Lux is a beauty soap capable of killing bacteria. This research uses Charles Sanders Peirce's semiotic analysis. Peirce's triadic model (representamen / sign + object + interpretant = sign) shows the big role of the subject in the process of language transformation. Based on the research results of the 99% Lux Botanicals advertisement Kills the bacteria of MaudyAyunda's version, the conclusions are as follows: (1) The meaning in the 99% Lux Botanicals advertisement Kills bacteria is actually Unilever's effort as a producer of Lux Botanicals to maintain its existence among Indonesians. (2) There are two shifting images in the advertisement of Lux Botanicals 99% Kill bacteria MaudyAyunda Version. The first is Lux's image, which was previously a luxurious beauty soap as a brand image, shifted to Lux Botanicals, a natural beauty soap. The second is the image of Lux which has shifted into Beauty soap which can kill bacteria where previously it was only beauty soap. (3) Ads for Lux Botanicals 99% Kill the bacteria of MaudyAyunda's version, the germs in question are bacteria. Aureus. Keywords : Shifting, Brand image, Advertising